1988
DOI: 10.1143/jjap.27.l1579
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition Behavior of Al-Y-Ni and Al-Ce-Ni Amorphous Alloys

Abstract: Ductile Al-Y-Ni and Al-Ce-Ni amorphous alloys were found to exhibit a glass transition at temperatures just below crystallization temperature. The glass transition temperature increases from 490 to 582 K with increasing solute concentration. The difference in specific heat between amorphous solid (AS) and supercooled liquid (SL) reaches 9.2 J/mol-K and the temperature coefficient of expansion and viscosity of the supercooled liquid are 100×10-5 K-1 and 3×1013 poise. By the transition of AS to SL, the Young's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 9 publications
4
42
0
Order By: Relevance
“…A larger DT x means a more stable supercooled liquid against crystallization and improved GFA. It has been observed that the Al-10Ce-Ni alloys show the higher thermal stability (T x : 500-730 K) than the Al-Ce10Ni alloys (402-620 K) [22,24]. This generally agrees with the better GFA and wider GFR (1-30 at% Ni) in the Al-10Ce-Ni alloys than that of the Al-Ce-10Ni alloys (2-10 at% Ce) [22,24].…”
Section: Gfa and The Heat Of Mixing For Liquidsupporting
confidence: 65%
See 2 more Smart Citations
“…A larger DT x means a more stable supercooled liquid against crystallization and improved GFA. It has been observed that the Al-10Ce-Ni alloys show the higher thermal stability (T x : 500-730 K) than the Al-Ce10Ni alloys (402-620 K) [22,24]. This generally agrees with the better GFA and wider GFR (1-30 at% Ni) in the Al-10Ce-Ni alloys than that of the Al-Ce-10Ni alloys (2-10 at% Ce) [22,24].…”
Section: Gfa and The Heat Of Mixing For Liquidsupporting
confidence: 65%
“…Among the various Al-based Al-Ce-M (M ¼ Fe, Co, Ni or Cu) alloys, the Al-Ce-Ni system is unique, which can be synthesized into a strong, flexible metallic glass with the widest GFR covering 2-15 at% Ce and 1-30 at% Ni [21][22][23][24][25]. It was found that the GFA and the thermal stability in the Al-rich corner were enhanced by increasing the solute content and specifically the Ce content [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to discuss the reason for the increase in ÁT x by the addition of the optimum B content (about 2 at%). As described above, the formation of a glassy phase in Al-Ni-Ce and Al-Ni-Y-Co systems has been interpreted 10,17) to result from the satisfaction of the three component rules, [18][19][20][21] i.e., (1) multi-component consisting of more than three elements, (2) significant atomic size mismatches above 12% among the main three elements, and (3) negative heats of mixing among their elements. The atomic size ratios of Al, Ce, Y, Ni and Co to B are 1.59, 2.03, 2.02, 1.39 and 1.39, 13) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since rapidly solidified Al-based fully or partially amorphous alloys with high strength and good ductility were discovered in the late 1980s [1][2][3] , considerable effort has been expended to develop the A1-Ni-RE systems due to their good glass-forming capability [4`s] .…”
Section: Introductionmentioning
confidence: 99%